Perancangan Aplikasi Korespondensi Rekam Medis Berbasis Web Di Rumah Sakit Bhayangkara Tk.1 Pusdokkes Polri - Rosita Putranto; Erix Gunawan (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
One of the activities of the medical record unit is correspondence, which is a correspondence activity related to medical records which includes medical resumes, insurance forms related to health services and medical certificates. According to the Minister of Health Regulation No. 21 of 2020, the Strategic Plan of the Ministry of Health for 2020-2024 concerning the Integration of Healtho Information Systems, it is stated that HIS is directed at strengthening health information services that are faster, valid, and resource sharing; consolidation of integrated electronic-based standard HIS; and strengthening the application of HIS in health care facilities. Related to this, it is a challenge for Bhayangkara Hospital Tk.1 Pusdokkes Polri to make changes, one of which is by making medical record correspondence applications to make it easier for users and service providers. So far, the correspondence process is still done manually so it takes a long time to complete the work. The information system that will be developed allows users to apply for correspondence anywhere and anytime without having to come directly to the Medical Record Installation of Bhayangkara Hospital Tk.1 Pusdokkes Polri. Furthermore, the officer will process the application and provide information to the user when the application is complete.